PERAN PENYULUH AGAMA ISLAM MEMBERIKAN EDUKASI AKHLAK TERHADAP REMAJA DI DESA JONGKONG KIRI TENGAH KECAMATAN JONGKONG - Asmawati, Asmawati; Sri Sunantri, Hifza (ILJ: Islamic Learning Journal, 2023)
This study focuses on the role of Islamic religious instructors in educating adolescents about association with a qualitative research approach and a type of case study research. The data collection technique that the authors use in this study is to use observation, interview and documentation techniques. Sources of data in this study were obtained from several respondents, namely teenagers, Muslim families with teenage children, Islamic religious counselors, the Office of Religious Affairs (KUA), the community, community leaders and religious leaders. The results of the study show that the role of Islamic religious instructors in providing education in the Jongkong community, especially for adolescents, is by providing teaching, guidance, exemplary, straightening the understanding of Islam. The method used by Islamic religious instructors in providing religious understanding for adolescents in Jongkong Kiri Tengah Village is by means of an individual approach, direct communication, group and indirect communication, while the Islamic religious education material delivered is about aqidah, worship, sharia and morals. While the form of coaching carried out by Islamic religious instructors in Jongkong Kiri Tengah Village includes (1) activating mosque youth activities, (2) activating sports activities.